Design, Analysis, and Control of Biomedical Healthcare Modular Wheelchair with Posture Transformation - Muhammad Zia Ur Rahman; Imran Ali; Asif Ishfaque; Muhammad Tanveer Riaz; Nasir Ahmad; M. M. Sayed Al Mahmud; Rimsha Tanveer (Complexity)
The majority of people with disabilities in the world have impairments that affect their lower bodies. In most of these cases, it was found that the affected person’s upper body was in good health and capable of carrying out all activities; however, the spinal cord injury results in significant health challenges with body functions like urination, bowel movements, heart rate, and respiratory, cardiovascular, and sexual function, which require prompt medical treatment and mobility aids. This study presents the mechanical layout of a wheelchair that can switch between a sitting and a standing position. The center of gravity must be taken into account when creating an electric standing wheelchair. It is designed specifically for people with disabilities to lessen the need of outside assistance, allowing the disabled person to savour a sense of adoration. In the simulation, the electric standing wheelchair analysis is carried out by loading with a human weight of 40 and 100 kg, and the transformation angle is adjusted between 0 and 90 degrees to compare the center of gravity displacement. SolidWorks and ANSYS are used to design the prototype, assemble the product, and establish the safety factor bounds of the structure and capabilities as required. The research focuses to achieve control of speed deviation and acceleration using a fuzzy control technique. The Arduino oversees the operation of the drive system as a controller, and a linear actuator is utilized for standing and sitting positions. This method is affordable, easily constructed, and highly secure.